A Review of the Interlanguage on Performance and Competence Representation: Universal Grammar - Qurrata 'Ain; Pratomo Widodo (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
Interlanguage has been the main development of field research on second language acquisition (SLA). According to Richard et al (1996) Interlanguage is one of the kinds of language that can be produced by second language learners in the process of acquiring or learning a new language. The influence of the universal grammar of the first language in learning the second language is still debated whether or not universal grammar takes part in second language acquisition. In this article has the aim to investigate the interlanguage of competence and performance representation. In second language acquisition, there is a confusion between the interlanguage of competence and performance. When people perform the second language, it will different from native speakers and argue that demonstrates defects in competence aspect. So, there is a lack of universal grammar. Interlanguage is natural when people acquire a second language based on the theory interlanguage. It might have the knowledge of grammar but when the people produced the sentence or words. It will be grammatical errors. There is some performance factor that the second language learners' competence is hidden such as parsing or demands of processing.  It differences between pure knowledge and how people use the knowledge of its self. Both of them do not always coincide. This research tried to offer a descriptive review of the Interlanguage on performance and competence representation.